(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
To discover the significant difference between two means after a significant ANOVA, the t test must be used. The estimated t value for private and public schools is 3.78, which is higher than the table value (3.78>2.58) at the 0.01 level of significance, as can be seen from table 4.7(c).